Synthesis and Characterization of Crown Ethers - KIRAZ, ASKIN; YILDIZ, MUSTAFA; DULGER, BASARAN (Asian Journal of Chemistry, 2010)
Crown ether ligands of Schiff base type (6-17) have been synthesized by the reaction of 2-hydroxybenzaldehyde, 2-hydroxy-5-methoxybenzaldehyde 2-hydroxy-5-bromobenzaldehyde, 2-hydroxy-5-chlorobenzaldehyde, 2-hydroxy-5-nitrobenzaldehyde and 2-hydroxy-1-naphthaldehyde with 6,7,8,14-tetrahydrodibenzo[f,i][1,5]dioxecine-2,12-diamine (4) and 7,9,10,16-tetrahydro-6H-dibenzo[h,k][1,4,7]-trioxacyclododecine- 2,14-diamine (5). The structures of Schiff base crown ethers have been investigated by elemental analysis, IR, UV-visible, 1H NMR, 13C NMR and MS spectroscopic data. In solution, all Schiff bases exist as equilibrium mixtures of enol-imine and keto-imine tautomers. For four Schiff bases (10, 11, 16, 17), the keto-imine form has been found to be dominant in the DMSO. The antimicrobial activities of the compounds are evaluated using disk diffusion method in dimethyl sulfoxide (DMSO) against 9 bacteria and 5 yeast cultures. The obtained results from disk diffusion method are assessed in side-by-side comparison with those of penicillin-G, ampicillin, cefotaxime, vancomycin, oflaxacin, tetracycline as antibacterial agents and nystatin, ketaconazole and clotrimazole as commercial antifungal agents. In most cases, the compounds show broad-spectrum (Gram-positive and Gram-negative bacteria) activities that are comparatively either, slightly less active or equipotent to, antimicrobial agents in the comparison tests.